Bringing Together Functional Classification and Business Process Analysis: Growing Trends in Records Management - Alberts, Inge; Schellinck, Jen; Eby, Craig; Marleau, Yves (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Drawing on our experience in developing business classifications, this communication identifies and discusses the challenges related to function-based approaches while proposing a methodology that reconciles the organizational perspective (i.e. the functional model) with the end-user perspective (i.e. the day-to-day tasks within a business process). Étayée par notre expérience dans le développement de systèmes de classification fonctionnelle, cette communication expose les défis inhérents à cette approche et propose une méthodologie qui réconcilie le point de vue organisationnel (c’est-à-dire le modèle fonctionnel) et le point de vue de l’utilisateur final (c’est-à-dire les tâches quotidiennes d'un processus d’affaires). ***Full paper in the Canadian Journal of Information and Library Science***